Sulfur Assimilation and Abiotic Stress in Plants - Khan, Nafees A (Springer, 2017)
Sulfur is one of the four major essential elements necessary for the plant life cycle. Its assimilation in higher plants and its reduction in metabolically important sulfur compounds are crucial factors determining plant growth and vigor and resistance to stresses. The range of biological compounds that contain sulfur is wide. The information on sulfur assimilation can be exploited in tailoring for efficient sulfur utilization, and in the applied approaches for the sustenance of agricultural productivity through nutritional improvement and increased stress tolerance.